2017
DOI: 10.7748/nop.2017.e961
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of lying and standing blood pressure in hospital

Abstract: Measuring lying and standing blood pressure (BP) is an important clinical observation in older hospital inpatients. This is because a drop in BP on standing, known as orthostatic hypotension (OH) is common in older people and in acute illness and, therefore, in hospital patients. OH increases the risk of a fall in hospital. Simple measures such as changes in medication or rehydration can reduce this drop in BP and reduce the risk of falls.In a recent snapshot audit in England and Wales of 179 acute hospitals a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The time needed for bedside staff to perform this assessment and the risk of measurement inaccuracy as a result of variations in time of day, device, and position influence the value of this assessment (Aydin et al, 2017; Cooke et al, 2009; Dind et al, 2011; McDonald et al, 2016; Soysal et al, 2016). Additionally, inadequate staff knowledge (Irvin & White, 2004; O’Riordan et al, 2017; Vloet et al, 2002), the need for more than one set of measurements and the fact that OH is often not reproducible challenge the usefulness of bedside OVS.…”
Section: The Problemmentioning
confidence: 99%
“…The time needed for bedside staff to perform this assessment and the risk of measurement inaccuracy as a result of variations in time of day, device, and position influence the value of this assessment (Aydin et al, 2017; Cooke et al, 2009; Dind et al, 2011; McDonald et al, 2016; Soysal et al, 2016). Additionally, inadequate staff knowledge (Irvin & White, 2004; O’Riordan et al, 2017; Vloet et al, 2002), the need for more than one set of measurements and the fact that OH is often not reproducible challenge the usefulness of bedside OVS.…”
Section: The Problemmentioning
confidence: 99%
“…In the 2015 national audit of inpatient falls (NAIF), Vasilakis et al (2015) identified that only 16% of 4846 eligible patients had an LSBP recorded by their third day in hospital. A review of the literature, which focused upon clinician knowledge and understanding of the correct OH measurement procedure, identified that in general, participating clinicians had poor knowledge of the OH measurement process, and the procedure they utilised to physically measure LSBP was inaccurate to diagnose OH ( Barsaiyan & Mildner, 2014 ; O’Riordan et al, 2017 ; Vloet et al, 2002 ). The participants were predominantly nurses, and some of the studies were dated so extrapolation of the findings to ambulance clinicians requires caution.…”
Section: Discussionmentioning
confidence: 99%
“…FIGURE 2: Documenting orthostatic blood pressure measurements [21] A retrospective audit of patients above the age of 60, admitted with a hip fracture secondary to a fall between August 10 and September 21, 2020, in the Orthopaedics department was undertaken to assess progress and compliance with set standards. Fifty-eight (58) patients (73% females) were included in this reaudit.…”
Section: Methodsmentioning
confidence: 99%